2015
DOI: 10.1371/journal.pone.0137254
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin Resistant Staphylococcus aureus among HIV Infected Pediatric Patients in Northwest Ethiopia: Carriage Rates and Antibiotic Co-Resistance Profiles

Abstract: BackgroundMRSA infections are becoming more prevalent throughout the HIV community. MRSA infections are a challenge to both physicians and patients due to limited choice of therapeutic options and increased cost of care.ObjectivesThis study was aimed to determine the prevalence of colonization and co-resistance patterns of MRSA species among HIV positive pediatric patients in the Amhara National Regional State, Northwest Ethiopia.MethodsCulture swabs were collected from the anterior nares, the skin and the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
27
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 32 publications
11
27
6
Order By: Relevance
“…High proportions of resistance to penicillin, erythromycin, clindamycin and tetracycline were found in MRSA isolates, which is similar to observed studies [23][24][25]. This finding suggests medical professionals should pay more attention to the rational use of these antibiotics.…”
Section: Discussionsupporting
confidence: 87%
“…High proportions of resistance to penicillin, erythromycin, clindamycin and tetracycline were found in MRSA isolates, which is similar to observed studies [23][24][25]. This finding suggests medical professionals should pay more attention to the rational use of these antibiotics.…”
Section: Discussionsupporting
confidence: 87%
“…First, we documented colonization with MRSA among PLWHA from inner São Paulo State. The point prevalence rate (2.4%) is not particularly high when compared to the international literature -where prevalence of up to 16.8% are reported [23]. In fact, our rate is lower than the pooled prevalence of 6.9% reported in a recent meta-analysis [33].…”
Section: Discussioncontrasting
confidence: 77%
“…Recent studies emphasize the intersection of HIV and CA-MRSA pandemics [19], [20], [21] Prevalence of colonization in this group is variable -with studies reporting rates ranging from similar to those reported for the general population [22] up to more than 16% [23].…”
Section: Introductionmentioning
confidence: 99%
“…Our prevalence of nasal carriage S. aureus was near about similar as reported by various others authors. 17,18 The Contrast finding was also reported by various authors. 3,19,20 Higher prevalence may be due to the immunocompromised status, frequent contact with both health care and community settings and frequent exposure to antibiotics; becoming them colonized with resistant strains which is also proposed by Hidron AI et al 4 Cefoxitin disc diffusion showed 100% specific (95% CI; 97.05%-100.00%), 100% sensitive (95% CI; 83.89%-00.00%) and 100% accurate (95% CI; 97.47% to 100.00%) method while comparing with gold standard mecA gene PCR.…”
Section: Discussionsupporting
confidence: 66%